Efficient flame-retardant artificial board, flame retardant and preparation method thereof
By using polyphosphate compounds, ammonium borate and boric acid as flame retardants in artificial boards, and using solution method combined with ultrasonic dispersion technology, the problem of poor flame retardant and mechanical properties of artificial boards is solved, efficient flame retardant and good mechanical properties are achieved, while reducing the release of harmful substances, which meets the requirements of green and environmental protection.
Patent Information
- Application Number
- CN202411781039.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-05
AI Technical Summary
The existing artificial boards have poor flame retardant properties and mechanical properties, and there is an odor of glue and paint during the production process, which affects environmental protection.
Polyphosphate compounds, ammonium borate and boric acid are used as flame retardants, and the flame retardant is uniformly dispersed in cellulose by solution method combined with ultrasonic dispersion technology, and sprayed and added to the raw materials of artificial boards, and then glued and hot-pressed.
It significantly improves the flame retardant and mechanical properties of artificial boards, reduces the release of harmful substances, meets the requirements of green and environmental protection, and complies with the GB/T 8624-2012 B1 grade flame retardant standard.
Smart Images

Figure CN119570498A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a man-made board, in particular to a high-efficiency flame-retardant man-made board, a flame retardant thereof and a preparation method thereof. Background Art
[0002] Wood-based panels are made of wood or other non-wood plants as raw materials. After being separated into various unit materials through certain mechanical processing, they are glued together with or without adhesives and other additives. They mainly include three categories of products, such as plywood, particleboard and fiberboard. There are hundreds of extended products and deep-processed products, which are widely used in construction engineering, interior decoration, furniture manufacturing, packaging and other industries. However, the raw materials included in wood-based panels are mostly plant fibers, which are combustible materials, so they are very easy to cause fires. It is reported that more than 21% of fires are caused by fiber materials such as wood, and 70% of fires in residential buildings are caused by the flammability of wood materials. Therefore, improving the flame retardant properties of wood-based panels is one of the measures to reduce the incidence of fires.
[0003] The flame retardant properties of existing artificial boards are mostly achieved by adding flame retardant ingredients into adhesives, mixing and stirring, and then evenly applying them between the board layers together with the adhesive. Although this method is simple to apply and the production cost of artificial boards is low, it has the following problems: 1) It is very easy for the flame retardant component and the adhesive to be incompatible, which will affect the uniformity of the flame retardant application, resulting in a decrease in the overall flame retardant effect of the wood-based panel and a decrease in the mechanical properties; 2) Including in the processing of the adhesive in the artificial board, it is coated between the boards, that is, the inside of the artificial board has flame retardant properties, but the board surface has no flame retardant components, which will lead to poor flame retardant effect of the board surface, affecting the overall fire prevention and flame retardant function of the artificial board; 3) Although the existing artificial boards use improved adhesives or improved surface environmentally friendly coatings, the finished artificial boards still have odors of glue and coatings, which will affect the comfort of people who touch the boards. If the odor cannot be removed for a long time, frequent breathing will affect people's health. Therefore, how to develop a green and environmentally friendly artificial board with high-efficiency flame retardant properties on the basis of meeting the mechanical properties of artificial boards has become the focus of current research. Summary of the invention
[0004] In view of the problems of the above-mentioned existing artificial boards having poor flame retardant effect, poor mechanical properties and environmental pollution, the present invention provides a high-efficiency flame retardant artificial board, its flame retardant and preparation method. The flame retardant artificial board has excellent flame retardant properties, good mechanical properties and low release of harmful substances, and meets green environmental protection requirements, and can be widely used in the fields of construction and home furnishing.
[0005] In order to achieve the above-mentioned object, the present invention provides a flame retardant for artificial panels, which comprises a polyphosphate compound, ammonium borate, boric acid and delignified biomass cellulose in a mass ratio of 5: (3-5): (2-5): (2-4).
[0006] When ammonium borate decomposes at high temperatures, it produces boron oxides and releases ammonia. This decomposition product helps to inhibit the spread of flames under high temperature conditions and can provide long-lasting flame retardant protection by generating a stable carbonized layer. The decomposition products of ammonium borate have the dual effects of suppressing flames and promoting carbonization. Through its ammonia release characteristics, ammonium borate helps to reduce temperatures and inhibit the formation of combustible gases, thereby enhancing the flame retardant effect. Ammonium borate and polyphosphate compounds can form stable inorganic compounds such as phosphoborates during pyrolysis. These compounds have strong stability at high temperatures and can further promote carbonization and enhance the flame retardant effect. Ammonium borate not only reacts with polyphosphate compounds, but also reacts with functional groups such as hydroxyl groups in delignified biomass cellulose to produce a more stable structure and enhance flame retardant properties.
[0007] The combination of polyphosphate compounds, ammonium borate and boric acid has the following advantages: 1) Synergistically enhance flame retardant properties Polyphosphate compounds (such as ammonium polyphosphate) can form a stable phosphate film during pyrolysis, which prevents the spread of flames and reduces heat conduction. When combined with boric acid and ammonium borate, the formation of boron oxide further enhances the stability of the carbonized layer, prevents the spread of flames and heat, and forms a more solid flame retardant protective layer.
[0008] The inorganic substances (such as boron oxide) produced by the decomposition of ammonium borate and boric acid strengthen the protective effect of the phosphate film and improve the flame retardant effect, especially at high temperatures, the flame retardant performance is more significant.
[0009] 2) Improve thermal stability Boric acid and ammonium borate decompose to generate boron oxides at high temperatures, which can effectively improve the heat resistance of the material and form a high-temperature resistant protective film. After being combined with polyphosphate compounds, the thermal stability of this film layer is further enhanced, improving the performance of the material in high-temperature environments.
[0010] This effect makes the composite system more advantageous than a single flame retardant system in a high temperature environment, avoiding the performance degradation caused by the instability of pyrolysis products.
[0011] 3) More stable flame retardant film layer When polyphosphate, boric acid and ammonium borate work together, the film layer formed is stronger. Boric acid and ammonium borate can promote the carbonization process of polyphosphate and generate a more stable carbonized layer, thereby reducing flame spread and gas release, and improving the flame retardant effect.
[0012] This film layer not only enhances the flame retardancy of the material, but also has a good reinforcement effect on the mechanical properties and durability of the material.
[0013] 4) Improved pyrolysis behavior and reduced harmful gas release Under high temperature conditions, the decomposition of polyphosphate compounds can release phosphate ions, and boric acid substances can produce boron oxides. These products work together to form a denser protective layer and reduce the release of harmful gases (such as CO, CO2, etc.).
[0014] In addition, the decomposition products of boric acid and ammonium borate can effectively capture or neutralize toxic gases, significantly reduce the emission of harmful substances during fires, and improve the environmental friendliness and safety of the materials.
[0015] 5) Enhance the mechanical properties of materials The addition of boric acid and ammonium borate may cross-link with polyphosphate through chemical reaction, thus enhancing the mechanical strength and stability of the material. This chemical cross-linking not only improves the heat resistance of the material, but also enhances the mechanical properties of the material such as compressive strength and tensile strength.
[0016] Compared with a single flame retardant system, the composite system combining the three can improve the comprehensive mechanical properties of the material while maintaining a good flame retardant effect, especially in high temperature environments.
[0017] Delignified biomass cellulose (such as wood fiber from poplar) is mainly composed of cellulose, lignin and a small amount of hemicellulose. In addition to being a carrier, it also interacts with other biomass fibers in the raw materials of artificial boards (such as wood fiber, bamboo fiber, etc.), especially during pyrolysis and flame retardant processes. The hydroxyl groups and other functional groups in these fibers react with flame retardants to enhance the flame retardant effect, and enhance the overall stability and fire resistance of the material through hydrogen bonding or other physical cross-linking. Delignified biomass cellulose not only plays a carrier role, but also works together with other fibers and flame retardants to improve the performance of the material.
[0018] Preferably, the polyphosphate compound is selected from one or more of ammonium polyphosphate, ammonium tripolyphosphate, and ammonium pyrophosphate, and the biomass fiber is selected from one or more of bamboo fiber, wood fiber, or straw fiber.
[0019] The second aspect of the present invention provides a method for preparing the flame retardant, which comprises the following steps: dissolving a polyphosphate compound, ammonium borate and boric acid in a cellulose solution, and then dispersing the cellulose solution to obtain a uniform flame retardant mixed solution.
[0020] Specifically, the dispersion treatment is performed by ultrasonic treatment at 20-40 kHz for 10-30 minutes at 30-40°C.
[0021] In the above technical scheme, polyphosphate compounds, ammonium borate and boric acid are compounded with cellulose through a solution method combined with ultrasonic dispersion technology, which significantly improves the uniform dispersion of the flame retardant material and effectively avoids the problem of flame retardant agglomeration. The prepared artificial board has excellent flame retardant properties.
[0022] Preferably, the mass fraction of the cellulose solution is 2-4%.
[0023] The third aspect of the present invention provides a method for preparing a high-efficiency flame-retardant artificial board, which comprises the following steps: adding the above-mentioned flame retardant to the raw materials of the artificial board by spraying, and stirring at the same time to ensure uniform distribution of the flame retardant; drying the mixed material, applying glue, and then hot pressing to obtain the said high-efficiency flame-retardant artificial board.
[0024] Preferably, the weight ratio of the flame retardant to the wood-based panel raw material is (1-15):100.
[0025] Specifically, the hot pressing temperature is 150-200° C., the pressure is 3-6 MPa, and the time is 20-30 minutes.
[0026] Preferably, the moisture content of the raw material is controlled below 8% before hot pressing.
[0027] The fourth aspect of the present invention provides a high-efficiency flame-retardant artificial board produced by the above-mentioned preparation method.
[0028] Through the above technical solution, the present invention achieves the following beneficial effects: 1. The flame retardant of the present invention utilizes the synergistic effect of polyphosphate compounds, ammonium borate and boric acid to significantly enhance the carbonization ability of artificial boards under high temperature conditions, forming a dense carbon layer, thereby effectively preventing the transfer of heat and oxygen, and greatly improving the flame retardant effect. The prepared green and efficient flame retardant artificial board has an oxygen index of more than 37%, which meets the GB / T 8624-2012 B1 flame retardant standard, and does not release toxic and harmful gases during combustion, and has good environmental performance.
[0029] 2. The present invention uses cellulose as a carrier of the flame retardant and combines the antioxidant properties of boric acid to not only improve the mechanical properties of the artificial board, but also improve its thermal stability, thereby achieving a good balance between flame retardancy and mechanical properties.
[0030] 3. In a preferred technical solution of the present invention, polyphosphate compounds, ammonium borate and boric acid are compounded with cellulose by a solution method combined with ultrasonic dispersion technology, which significantly improves the uniform dispersion of the flame retardant material and effectively avoids the problem of flame retardant agglomeration. The prepared artificial board has excellent flame retardant properties.
[0031] 4. The artificial board prepared by the present invention uses biomass fiber as the raw material source, which is both environmentally friendly and renewable, reduces production costs, conforms to the concept of sustainable development, and provides a new idea for the high added value utilization of traditional artificial boards.
[0032] 5. The preparation process of the present invention is simple and easy, the raw materials are widely available, and it is suitable for industrial production. At the same time, it gives the artificial board high-efficiency flame retardant properties, broadening its application range in the fields of construction, home furnishing, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 is a TEM image of a cellulose solution of the present invention mixed with a polyphosphate compound, ammonium borate and boric acid; Figure 2 is a thermogravimetric analysis (TGA) curve of the green and efficient flame-retardant artificial board obtained in Example 1 of the present invention; Figure 3 This is the bending stress-strain curve of the green and efficient flame-retardant artificial board obtained in Example 1 of the present invention. DETAILED DESCRIPTION
[0034] The specific implementation of the present invention is described in detail below in conjunction with the examples. It should be understood that the specific implementation described herein is only used to illustrate and explain the present invention, and is not used to limit the present invention.
[0035] Example 1 The preparation method of the high-efficiency flame-retardant artificial board is as follows: 1) After bamboo fiber (length controlled within the range of 2-5 cm) was soaked in ammonia water for 12 hours, it was delignified with 2M sodium hydroxide and 1M sodium sulfite, washed to neutrality, and bleached with 3% hydrogen peroxide to obtain cellulose raw material.
[0036] 2) 4 g of cellulose was dispersed in 196 mL of deionized water and treated with an ultrasonic crusher (frequency 25 kHz, temperature 30°C) for 30 minutes to obtain a cellulose solution. 3) 10g of ammonium polyphosphate, 6g of ammonium borate and 4g of boric acid were added to the cellulose solution prepared in step 2) and treated with an ultrasonic oscillator (frequency 30kHz, temperature 35°C) for 20 minutes until the flame retardant was evenly dispersed to obtain a flame retardant mixed solution. From the SEM image ( Figure 1 ) It can be seen that the flame retardant is evenly distributed and firmly bound to the cellulose surface.
[0037] 4) Spray 200g of the flame retardant mixture evenly on 1300g of medium density fiberboard raw material (MDF), stir evenly, and air-dry at 60°C until the moisture content is less than 8%.
[0038] The above medium density fiberboard (MDF) raw materials include: Sawdust: A mixture of bark and sawdust, with particle size of about 0.2~1.5mm, accounting for about 80%-85% of the raw materials.
[0039] Binder: Urea-formaldehyde resin (UF) is used as a binder, with a content of 10% to 12% of the mass of the sawdust. Urea-formaldehyde resin can form a strong bond with the sawdust under heating, providing excellent structural stability.
[0040] Moisture content: Before spraying the flame retardant mixture, the moisture content of the wood chips and binder mixture is about 8%~10%.
[0041] 5) The mixed raw materials are treated with glue, and hot-pressed at a pressure of 3 MPa and a temperature of 150° C. for 30 minutes using hot-pressing equipment to produce a green and highly efficient flame-retardant artificial board.
[0042] 6) Oxygen index test results show that the oxygen index of artificial board reaches more than 37%, and the flame retardant performance is excellent; the thermogravimetric analysis results are as follows Figure 2 As shown, it shows that the artificial board has excellent thermal stability; the bending stress-strain curve is shown in Figure 3 As shown, it shows that artificial boards have excellent mechanical properties and are suitable for high-standard flame retardant materials in the fields of construction and home furnishing.
[0043] Example 2 The preparation method of the high-efficiency flame-retardant artificial board is as follows: 1) After soaking the straw fiber in ammonia water for 24 hours, it was delignified with 5M sodium hydroxide and 2.5M sodium sulfite, washed to neutrality, and then bleached with 3% hydrogen peroxide to obtain purified cellulose raw material.
[0044] 2) 8 g of cellulose was dispersed in 192 g of deionized water and treated with an ultrasonic crusher (frequency 20 kHz, temperature 40°C) for 20 minutes to obtain a cellulose solution.
[0045] 3) 10 g of ammonium tripolyphosphate, 10 g of ammonium borate and 10 g of boric acid were added to the cellulose solution prepared in step 2), and treated with an ultrasonic oscillator (frequency 20 kHz, temperature 30° C.) for 30 minutes until the flame retardant was evenly dispersed to obtain a flame retardant mixed solution.
[0046] 4) Spray 150g of the flame retardant mixture evenly on 1300g of particleboard raw materials, stir evenly, and air-dry in a 50°C environment until the moisture content is less than 8%.
[0047] The above particleboard raw materials include: Sawdust and wood shavings: Mainly use mixed sawdust of coniferous wood and hardwood, among which the particle size distribution of sawdust particles is between 1 and 3 mm, accounting for about 75% to 80% of the raw materials.
[0048] Binder: Phenolic resin (PF) is used as a binder, and the amount of resin added is 10% to 15% of the wood chips. Phenolic resin can provide good water resistance and strength at high temperatures and is a commonly used binder for making particleboard.
[0049] Moisture content: After mixing sawdust, wood shavings and binder, the moisture content is about 6%~8%. 5) After the treated raw materials are sizing, hot pressing is carried out at 6MPa pressure and 170°C temperature for 25 minutes to produce green and efficient flame retardant artificial board.
[0050] 6) The oxygen index test results show that the oxygen index of the artificial board reaches 39%, with excellent thermal stability; the flame retardant properties and mechanical properties meet the high standards of flame retardant grade of building materials, and are suitable for interior decoration and high-safety application scenarios.
[0051] Example 3 The preparation method of the high-efficiency flame-retardant artificial board is as follows: 1) After soaking poplar fiber in ammonia water for 24 hours, it was delignified with 5M sodium hydroxide and 2.5M sodium sulfite, washed to neutrality, and then bleached with 3% hydrogen peroxide to obtain purified cellulose raw material.
[0052] 2) 6 g of cellulose was dispersed in 194 mL of deionized water and treated with an ultrasonic crusher (frequency 40 kHz, temperature 40°C) for 20 minutes to obtain a cellulose solution.
[0053] 3) 5 g of ammonium tripolyphosphate, 5 g of ammonium pyrophosphate, 8 g of ammonium borate and 6 g of boric acid were added to the cellulose solution prepared in step 2), and treated with an ultrasonic oscillator (frequency 40 kHz, temperature 40°C) for 10 minutes until the flame retardant was evenly dispersed to obtain a flame retardant mixed solution.
[0054] 4) Spray 130 mL of the flame retardant mixture evenly on 1300 g of plywood raw material, stir evenly, and air-dry in an environment of 50°C until the moisture content is less than 8%.
[0055] The above plywood raw materials include: Wood veneer: veneer made of poplar or pine, the thickness of the veneer is 1.5~3mm, and the arrangement direction of each layer of veneer is alternating.
[0056] Adhesive: Polyurethane glue (PU) is used as the adhesive, and the content is 8%~10% of the mass of the wood veneer. Polyurethane glue has good water resistance and excellent bonding strength, and is suitable for the production of plywood.
[0057] Moisture content: After spraying the flame retardant mixture, the moisture content of the plywood substrate is about 5%~7%.
[0058] 5) After the treated raw materials are glued, they are hot-pressed at a pressure of 3 MPa and a temperature of 200° C. for 20 minutes to produce a green and efficient flame-retardant artificial board.
[0059] 6) The oxygen index test results show that the oxygen index of the artificial board reaches 37%, with excellent thermal stability; the flame retardant properties and mechanical properties meet the high standards of flame retardant grade of building materials, and are suitable for interior decoration and high-safety application scenarios.
[0060] Comparative Example 1 The medium density fiberboard in Example 1.
[0061] Comparative Example 2 Other conditions are the same as those in Example 1, except that step 3 is omitted). The oxygen index of the artificial board is measured to be only 21%.
[0062] Comparative Example 3 Other conditions were the same as in Example 1, except that the flame retardant in step 3) was changed to 20 g of ammonium polyphosphate. The oxygen index of the artificial board was measured to be only 25%.
[0063] Comparative Example 4 Other conditions were the same as in Example 1, except that the flame retardant in step 3) was changed to 20 g of boric acid. The oxygen index of the artificial board was measured to be only 26%.
[0064] Comparative Example 5 Other conditions were the same as in Example 1, except that the flame retardant in step 3) was changed to 20 g of ammonium borate. The oxygen index of the artificial board was measured to be only 29%.
[0065] Comparative Example 6 The other conditions were the same as those in Example 1, except that the raw material was not delignified. The oxygen index of the artificial board was measured to be only 33%, and the thermal stability and mechanical properties were poor.
[0066] Thermal stability: Undelignified raw materials contain higher levels of lignin, which results in poor thermal stability of the board during heating. Lignin decomposes earlier during pyrolysis and releases more volatile gases (such as phenols, etc.), making it easier to spread the flame in case of fire. Therefore, undelignified raw materials will show lower thermal stability and flame retardant effect than delignified raw materials.
[0067] Flame retardant properties: The presence of lignin will affect the dispersibility and reactivity of flame retardants (such as polyphosphate compounds, boric acid, etc.), reducing the flame retardant effect. Since the decomposition of lignin will increase the release of harmful gases, it will affect the flame retardant properties of the board.
[0068] Mechanical properties: In the raw materials without delignification, lignin as a natural organic polymer provides a certain rigidity and support, but due to the uneven structure of lignin, the mechanical properties of the board are not as stable as those of the delignified material. Therefore, the raw materials without delignification show lower strength and toughness.
[0069] Comparative Example 7 Other conditions were the same as in Example 1, except that 10 g of ammonium polyphosphate and 10 g of ammonium borate were used in step 3), and no boric acid was used. The oxygen index of the artificial board was measured to be only 33%, and the thermal stability and mechanical properties were poor.
[0070] Flame retardant properties: Boric acid plays an important role in flame retardant systems. Especially at high temperatures, it can form flame retardant borates and help generate a carbonized layer to inhibit the spread of flames. If boric acid is not added, the flame retardant effect of the entire system will be weakened. Although ammonium polyphosphate and ammonium borate both have certain flame retardant effects, the lack of boric acid may result in a carbonization effect that is not as expected, thereby reducing the flame retardant effect of the board.
[0071] Thermal stability: Due to the lack of boric acid, the thermal stability of the board under high temperature conditions will be affected. Boric acid can help form a protective carbonization layer at high temperatures, delaying the pyrolysis process, thereby improving thermal stability. Without boric acid, ammonium polyphosphate and ammonium borate are not effective enough to form this protective layer, resulting in poor thermal stability.
[0072] Mechanical properties: The lack of boric acid will also affect the mechanical properties, especially during the formation and pyrolysis of the flame retardant layer, the stability and strength of the carbonized layer are low, thus affecting the overall strength of the board.
[0073] Comparative Example 8 Other conditions were the same as those in Example 1, except that 10 g of ammonium polyphosphate and 10 g of boric acid were used in step 3) instead of ammonium borate. The oxygen index of the artificial board was measured to be only 30%, and the thermal stability and mechanical properties were poor.
[0074] Flame retardant properties: Ammonium borate is a common flame retardant that can release ammonia by decomposition, helping to reduce the spread of flames at high temperatures. At the same time, it can react with other inorganic components (such as polyphosphates) to form a stable carbonized layer. If ammonium borate is not added, the flame retardant effect will be reduced, especially in the early stages of a fire, the lack of ammonia's inhibitory effect may cause the flame to spread faster. Although boric acid itself has a certain flame retardant effect, the synergistic effect of boric acid and ammonium polyphosphate is not as strong as the synergistic effect of ammonium borate and ammonium polyphosphate. The lack of ammonium borate leads to a further weakening of the flame retardant effect.
[0075] Thermal stability: Ammonium borate can decompose to generate ammonia, which helps to reduce the temperature and reduce the pyrolysis rate, thus improving the thermal stability of the material. In the absence of ammonium borate, although boric acid and ammonium polyphosphate can also play a certain role, they lack the temperature control effect of ammonia release, resulting in relatively poor thermal stability.
[0076] Mechanical properties: Similarly, the absence of ammonium borate affects mechanical properties because it enhances the strength and stability of the char layer. Without ammonium borate, the formation of the char layer may be incomplete or unstable, thus affecting mechanical properties, especially strength retention at high temperatures.
[0077] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0078] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0079] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A flame retardant for artificial boards, characterized in that: It includes polyphosphate compounds, ammonium borate, boric acid and delignified biomass cellulose in a mass ratio of 5:(3-5):(2-5):(2-4).
2. The flame retardant according to claim 1, characterized in that The polyphosphate compound is selected from one or more of ammonium polyphosphate, ammonium tripolyphosphate, and ammonium pyrophosphate, and the biomass fiber is selected from one or more of bamboo fiber, wood fiber, or straw fiber.
3. The method for preparing the flame retardant according to claim 1 or 2, characterized in that: The method comprises the following steps: dissolving polyphosphate compounds, ammonium borate and boric acid in a cellulose solution, and then dispersing the cellulose solution to obtain a uniform flame retardant mixed solution.
4. The preparation method according to claim 3, characterized in that: The dispersion treatment is carried out by ultrasonic treatment at 20-40 kHz for 10-30 minutes at 30-40°C.
5. The preparation method according to claim 3, characterized in that: The mass fraction of the cellulose solution is 2-4%.
6. A method for preparing a highly efficient flame-retardant artificial board, characterized in that: The method comprises the following steps: adding the flame retardant described in claim 1 or 2 to the raw material of the artificial board by spraying, and stirring at the same time to make the flame retardant evenly distributed; drying the mixed material, applying glue, and then hot pressing to obtain the high-efficiency flame-retardant artificial board.
7. The preparation method according to claim 6, characterized in that: The weight ratio of the flame retardant to the raw material of the artificial board is (1-15):
100.
8. The preparation method according to claim 6, characterized in that The hot pressing temperature is 150-200° C., the pressure is 3-6 MPa, and the time is 20-30 minutes.
9. The preparation method according to claim 6, characterized in that: The moisture content of the raw materials was controlled below 8% before hot pressing.
10. A high-efficiency flame-retardant artificial board prepared by the preparation method according to any one of claims 6 to 9.
Citation Information
Patent Citations
Method of treating fire retardant wood using microwave
CN101306547A
Method for preparing fiberboard composite flame retardant
CN101961879A
Environment-friendly smoke suppression and flame retardance medium-density fiberboard and preparation method thereof
CN108247808A
Flame retardant for plywood glue and application of flame retardant
CN110065119A
Delignified wood materials, and methods for fabricating and use thereof
CN111417499A
Cited By
Continuous processing method of bamboo fiber composite board
CN120422326A